In vitro antifungal activity and phytochemical characterization of Eugenia uniflora, Libidibia ferrea and Psidium guajava - Magda Rhayanny Assunção Ferreira; Rosilene Rodrigues Santiago; Walicyranison Plínio Silva-Rocha; Luanda Barbara Ferreira Canário de Souza; Maria Graciela Icher Faria; João Carlos Palazzo de Mello; Silvana Maria Zucolotto Langassner; Guilherme Maranhão Chaves; Eveline Pipolo Milan; Terezinha Inez Estivalet Svidzinski; Luiz Alberto Lira Soares (Universidade de São Paulo, 2021)
The aim of this study was evaluate the in vitro antifungal activity of crude extracts from Eugenia uniflora, Libidibia ferrea and Psidium guajava. The extracts were obtained by turbo-extraction using water (AQ) or acetone-water (AC-W) (7:3, v/v) as solvents and lyophilized to obtain the crude extracts (CE). The CE were characterized by UV-Vis, TLC and HPLC. The activity of CEs was investigated against clinical isolates of Candida spp. and the Minimum Inhibitory Concentration (MIC), MIC50 and MIC90 were determinated. The analysis by TLC showed that all CEs presented polyphenols (flavonoids and tannins). The CEs from E. uniflora showed higher amount of polyphenols (30.35 ± 2.15%, AC-W) and the HPLC analysis revealed the tannins in all extracts. The CEs of E. uniflora showed MIC range from 1.9 to 500.0 µg/mL, and lower values of MIC50 and MIC90 against non-albicans Candida isolates. Regarding L. ferrea and P. guajava, the results showing MIC from 3.9 to 1000.0 µg/mL (CE-AQ) against C. albicans. The results demonstrate antifungal performance from CE against various species of Candida spp., suggesting that the herbal species may be use as new potential antifungal agents. Additionally, the polyphenol content can play a pivotal role in the antifungal properties of CE.